Evaluation of the Community-Based Hypertension Management Programs in China - Hao, Guang; Chen, Zuo; Wang, Xin; Zhang, Linfeng; Kang, Yuting; Zheng, Congyi; Chen, Lu; Wang, Zengwu; Gao, Runlin (Frontiers in Public Health, 2022)
Purpose The National Essential Public Health Services Package (NEPHSP), a set of community-based hypertension management programs, was launched by the Chinese government in 2009. However, the data are limited for the comprehensive evaluation of NEPHSP on hypertension management. This study was to estimate the effect of NEPHSP on hypertension control nationwide in China. Methods Data were from China Hypertension Survey (CHS). The participants (n = 119,412) aged ≥35 years with hypertension were included in the analysis. Further, a subset of 64,188 diagnosed hypertensive patients were analyzed to evaluate the effect of NEPHSP by comparing the ones covered and not covered by NEPHSP. Blood pressure (BP) was measured by trained staff using a validated digital portable monitor in local communities or clinics. Results Among adults aged ≥35 years with hypertension, the coverage of NEPHSP was 25.6% and increased with age. The coverage was significantly higher in women than in men (P < 0.001). Among the 64, 188 diagnosed hypertensive patients, compared to the control group (not covered by NEPHSP), the mean systolic and diastolic BPs were 2 mmHg and 1.6 mmHg lower in NEPHSP group, respectively. The rate of treatment for hypertension was significantly higher in NEPHSP group than the control group (93.0% vs. 81.4%, P < 0.001), and the rate of BP control was also significantly higher in NEPHSP group than the control group (35.9% vs. 29.6%, P < 0.001). Furthermore, similar trends were found in rural and urban, as well as in men and women. Conclusions Our results showed that NEPHSP is effective in improving hypertension treatment and control in hypertensive patients in China. However, the coverage of NEPHSP was still low.